2005
DOI: 10.1115/1.1852484
|View full text |Cite
|
Sign up to set email alerts
|

Immiscible Liquid-Liquid Displacement in Capillary Tubes

Abstract: We analyze the liquid-liquid displacement in capillary tubes. The goal is to determine the amount of displaced liquid that remains attached to the tube wall and the configuration of the liquid-liquid interface at different operating parameters. The study encompasses both numerical and experimental approaches. The finite element method is used to solve the governing equations and, in order to validate the predictions, visualization experiments are performed to capture images of the interface. The numerical resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…Similar experiments were also fulfilled by Soares et al [36] with the use of two immiscible liquids. They noted that air (or an injected liquid in the case of Soares et al) breaks through the center part of the tube's cross-section, and some amount of the liquid, that initially occupied the tube, remains on the tube's walls.…”
Section: Introductionsupporting
confidence: 65%
“…Similar experiments were also fulfilled by Soares et al [36] with the use of two immiscible liquids. They noted that air (or an injected liquid in the case of Soares et al) breaks through the center part of the tube's cross-section, and some amount of the liquid, that initially occupied the tube, remains on the tube's walls.…”
Section: Introductionsupporting
confidence: 65%
“…Fig. 5 also shows a comparison for the shear-thinning power-law liquid with behavior index n = 0.652 with two different meshes: one with 240 elements, 1035 nodes and 4860 degrees of freedom generated in a previous work by Soares et al [21] and another with 900 elements, 3801 nodes and 17,904 degrees of freedom generated in the present work. The results obtained with the finer mesh show a continuous tendency of departure from the Newtonian behavior as the capillary number is decreased.…”
Section: Preliminary Resultsmentioning
confidence: 93%
“…In this method, the physical domain is mapped onto a computational fixed reference frame where the partial differential equations for each dimension considered are solved. Recent examples of interesting complex problems in which this technique has been applied are found in Romero et al [20], who studied the problem of the low-flow limit in slot coating, and Soares et al [21], who studied the liquid-liquid displacement of Newtonian fluids, among others.…”
Section: Introductionmentioning
confidence: 98%
“…They observed that the layer thickness decreases as the yield stress of the displaced liquid is increased. More recently, Soares et al [19] analyzed, using finite-element simulations and experiments, the steady displacement of a viscous liquid by a long drop of another viscous liquid in a capillary tube, for a wide range of the capillary number and viscosity ratio. Their theoretical predictions and flow visualization experiments showed the effect of different parameters on the interface configuration and on the thickness of the layer of the displaced liquid left on the walls.…”
Section: Introductionmentioning
confidence: 99%